POSITIVE POLITENESS STRATEGIES USED IN THE COMMENT SECTION OF ALINAKIM’S TIKTOK - Ivana Merry Aprilia; Christina Maya Iriana Sari (Humaniora Scientia, 2023)
This study aims to analyze the positive politeness strategies used in the comment section of Alinakim's TikTok account. The objectives of this study are to identify the types of positive politeness strategies used and to explain the purpose of those strategies. This study uses a qualitative approach with a descriptive design. The data were collected from the comment section of Alinakim's TikTok account. This study aims to analyze the positive politeness strategies used by users in the comments section of the @Alina Kim account on TikTok by utilizing the theory of Brown and Levinson (1987). This study method used in this study is qualitative research. The data and source of data are collected from the comment section of Alinakim's TikTok videos in December 2022. The findings of this study show that the dominant positive politeness strategies used in the comment section are intensifying interest and giving compliments. These strategies aim to enhance the hearer's positive face, making them feel good about themselves. These strategies aim to create a positive and supportive environment, which is essential in building a sense of community and belonging. The conclusion, the positive politeness strategies used in the comment section of Alinakim's TikTok , particularly the strategies of intensifying interest and giving compliments, are effective in creating a positive and supportive relationship. The findings suggest that positive politeness strategies play a crucial role in the construction of social relations in online communities because they help to establish rapport, create an atmosphere of mutual interest, promote discussion, strengthen groups, and maintain politeness in online interactions. Keywords: Positive Politeness Strategies, Comment Section, TikTok.